Molecular and Morphological Identification and Seasonal Distribution of Eggs of Four Decapterus Fish Species in the Northern South China Sea: A Key to Conservation of Spawning Ground - Hou, Gang; Wang, Jinrun; Chen, Zuozhi; Zhou, Jinlong; Huang, Wangsu; Zhang, Hui (Frontiers in Marine Science, 2020)
Although species of Decapterus form important pelagic fisheries in the northern South China Sea, information on their spawning grounds is limited because identification of fish eggs based on their morphology is difficult. We identify eggs of four Decapterus species (D.macrosoma, D.maruadsi, D.macarellus, and D.tabl) with DNA barcodes from the fishery resources surveys in Spring and Autumn 2018 in Xisha islands, and Spring and later summer-Autumn 2019 along the continental shelf of the northern South China Sea, and describe egg morphology. Of 1405 fish eggs with obtained COI sequences, 81 were successfully attributed to four Decapterus species; eggs of each are spherical, have a smooth chorion and narrow perivitelline space, and can be partly differentiated by diameter, melanophore drops on the oil globule, and the notum of the embryo. Seasonal distributions of eggs reveal spawning grounds, with that of D.maruadsi located mainly off the Pearl River estuary in spring; eggs of D. maruadsi rarely co-occur with those of D.macrosoma. Spawning grounds of D.macrosoma are probably further south, where water temperature and salinity are higher. Spawning periods of these four Decapterus species overlap slightly. Spawning habitat D.maruadsi has been lost, and the spawning season of D.macrosoma has extended. Identification of Decapterus eggs using DNA barcodes can assist with the identification of eggs using traditional morphological approaches. Spatial and temporal information on the distributions of Decapterus eggs can be used for improved conservation of spawning grounds and fisheries management in the northern South China Sea.